2019
DOI: 10.1073/pnas.1901730116
|View full text |Cite
|
Sign up to set email alerts
|

Post-stress bacterial cell death mediated by reactive oxygen species

Abstract: Antimicrobial efficacy, which is central to many aspects of medicine, is being rapidly eroded by bacterial resistance. Since new resistance can be induced by antimicrobial action, highly lethal agents that rapidly reduce bacterial burden during infection should help restrict the emergence of resistance. To improve lethal activity, recent work has focused on toxic reactive oxygen species (ROS) as part of the bactericidal activity of diverse antimicrobials. We report that when Escherichia coli was subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
275
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(291 citation statements)
references
References 62 publications
14
275
1
1
Order By: Relevance
“…Recently, a report showed that bacteria lacking the AhpF/C system suffer a severe post-stress recovery. The absence of the AhpF/C system also contributes to the lethality of the mutants probably by the inability of the cell to cope with a low level of ROS after severe oxidative stress [34]. Another protein that illustrates an important influence on priming response is RecA, with the mutant showing a decreased priming response to H 2 O 2 .…”
Section: Priming Response Is Compromised By Disrupting Important H 2 mentioning
confidence: 99%
“…Recently, a report showed that bacteria lacking the AhpF/C system suffer a severe post-stress recovery. The absence of the AhpF/C system also contributes to the lethality of the mutants probably by the inability of the cell to cope with a low level of ROS after severe oxidative stress [34]. Another protein that illustrates an important influence on priming response is RecA, with the mutant showing a decreased priming response to H 2 O 2 .…”
Section: Priming Response Is Compromised By Disrupting Important H 2 mentioning
confidence: 99%
“…However, promptly after the nalidixic acid is washed away, DNA synthesis resumes (12). Based on mass spectrometry quantification, Hong et al (10) measure a decrease in intracellular nalidixic acid concentration to 0.002 MIC after washing and diluting treated cells. The second feature of the system is crucial for determining whether cells die when the antibiotic remains inside the cell or, alternatively, when cells are free of the antibiotic.…”
Section: Time After Addition Of Antibioticmentioning
confidence: 99%
“…For UV irradiation, the repair of primary damage by photolyase proved instrumental for this important distinction. For nalidixic acid treatment, Hong et al (10) discover that the sequestration of a secondary damaging agent, rather than repair of the primary damage, is essential. Specifically, a higher tolerance level is measured when compounds preventing the accumulation of reactive oxygen species (ROS) are added to the recovery plate ( Fig.…”
Section: Time After Addition Of Antibioticmentioning
confidence: 99%
See 2 more Smart Citations